Discrete-time and continuous-time generalised predictive controllers with anticipated filtration: Tuning rules - Kowalczuk, Zdzisław; Suchomski, Piotr; Marcińczyk, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
A general class of control algorithms based on the generalised predictive control (GPC) strategy with anticipated filtering (AF) of the control error is considered in both the discrete- and continuous-time domains. It is shown that in the discrete-time settings, under certain conditions, a solution of the AF-GPC design always exists and the design leads to stable control systems with definite closed-loop characteristics.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka